3D Printed Li–S Batteries with In Situ Decorated Li2S/C Cathode: Interface Engineering Induced Loading‐Insensitivity for Scaled Areal Performance. Issue 14 (3rd March 2021) - Xue, Lanxin; Zeng, Li; Kang, Wenbin; Chen, Haiyan; Hu, Yin; Li, Yaoyao; Chen, Wei; Lei, Tianyu; Yan, Yichao; Yang, Chengtao; Hu, Anjun; Wang, Xianfu; et al.
Abstract: Holding manifold advantages including environmental benignity, enhanced structural robustness, and high capacity, Li2 S as a competitive substitute of sulfur in Li–S batteries is receiving escalating attention. However, serious issues rooted in its intrinsic poor conductivity and sluggish mass transport present the significant challenge of achieving high active material use with appealing kinetics for effective scaling in areal capacitance under elevated loading densities. This renders current Li2 S cathodes incapable of securing energy availability that responds to power‐hungry modern electronics. Here for the first time, an interfacial engineering approach is devised by in situ decorating a 3D printed carbonaceous scaffold with uniform surface‐deposited Li2 S and by healing the printed adjacent interface to eliminate the interfacial resistance. As a result, facile mass transport throughout the whole printed matrix is enabled. 3D printed electrodes with high active material use and loading‐insensitive performance delivering outstanding areal capacity and fast kinetics of 6.29 mAh cm −2 at 6 mA cm −2 under an impressive loading density of 10 mg cm −2 are realized, which are among the best results reported for Li2 S‐based batteries. The thrilling performance points to a highly effective approach that advances the performance of Li2 S cathodes closer toward real‐world applications. Abstract : An interfacial engineering approach by in situ decorating a 3D printed carbonaceous scaffold with uniform surface‐deposited Li2 S is devised for Li–S batteries. As a result, the 3D printed Li2 S electrodes featuring high active material use, and loading‐insensitive performance deliver outstanding areal capacity.